Signals Sampling Theorem

Download as pdf or txt
Download as pdf or txt
You are on page 1of 3

1/23/2020 Signals Sampling Theorem - Tutorialspoint

Signals Sampling Theorem

Statement: A continuous time signal can be represented in its samples and can be recovered back
when sampling frequency fs is greater than or equal to the twice the highest frequency component of
message signal. i. e.

f
fs ≥ 2f m..
s ≥ 2fm

Proof: Consider a continuous time signal x(t). The spectrum of x(t) is a band limited to fm Hz i.e. the
spectrum of x(t) is zero for |ω|>ωm.
Sampling of input signal x(t) can be obtained by multiplying x(t) with an impulse train δ(t) of period Ts.
The output of multiplier is a discrete signal called sampled signal which is represented with y(t) in the
following diagrams:

Here, you can observe that the sampled signal takes the period of impulse. The process of sampling
can be explained by the following mathematical expression:

Sampled
Sampled signal
signal y
y((t
t)) =
= x
x((t
t)).. δ
δ((t
t)) .. .. .. .. .. .. (
(11)
)

The trigonometric Fourier series representation of δ


δ (t) is given by

https://www.tutorialspoint.com/signals_and_systems/signals_sampling_theorem.htm 1/3
1/23/2020 Signals Sampling Theorem - Tutorialspoint



δ
δ((t
t)) =
= a
a0 + Σ
0 + Σ
(
(aan cos nω s t
n cos nωs t++b
bn sin nω s t
n sin nωs t)) .. .. .. .. .. .. (
(22)
)
n
n==1
1

T
T

Where a
a0 =
0 = T
1
1

∫−−T
T
2
2
δ
δ((t
t))d
dtt =
=
1
1

T
δ
δ((0
0)) =
=
T
1
1

Tss Tss Tss


2
2

T
T

2
2 2
2 2
2 2
2
a
an =
n =

∫−−T
T
δ
δ((t
t)) cos
cos n
nωωs dt =
s dt =
δ
δ((0
0)) cos
cos n
nωωs 0 =
s0 =
T
Tss
T
T22
T
T
2
2

T
T

2
2 2 2
2
b
bn =
n =

∫−
2
−T
T
δ
δ((t
t)) sin
sin n
nωωs t dt =
s t dt =
δ
δ((0
0)) sin
sin n
nωωs 0 = 0
s0 = 0
T
Tss
T
Tss
2
2

Substitute above values in equation 2.

1
1 ∞
∞ 2
2

∴ δ
δ((t
t)) =
= +
+ΣΣ (
( cos
cos n
nωωs t + 0)
s t + 0)
T
Ts n
n==1
1 T
Ts
s s

Substitute δ(t) in equation 1.


→ y
y((t
t)) =
= x
x((t
t)).. δ
δ((t
t))

1
1 ∞
∞ 2
2
=
= x
x((t
t))[[ +
+ΣΣ (
( cos
cos n
nω t)]
s t)]
ωs
T
Ts n
n==1
1 T
Ts
s s

1
1 ∞ ∞
=
= [[x
x((t
t))+
+22Σ
Σ (
(cos
cos n
nωωs t
t))x
x((t
t))]]
T n
n==1
1 s
Tss

1
1
y
y((t
t)) =
= [[x
x((t
t))+
+22 cos
cos ω
ωs t
t.. x
x((t
t))+
+22 cos
cos 2
2ωωs t
t.. x
x((t
t))+
+22 cos
cos 3
3ωωs t
t.. x
x((t
t)) .. .. .. .. .. .. ]]
T s s s
Tss

Take Fourier transform on both sides.

1
1
Y
Y((ω
ω)) =
= [[X
X((ω
ω))+
+XX(
(ωω−
−ωωs )
)++X
X((ω
ω++ω
ωs )
)++X
X((ω
ω−−2
2ωωs )
)++X
X((ω
ω++2
2ωωs )
)++ .. .. .. ]]
T s s s s
Tss

1
1 ∞


∴ Y
Y((ω
ω)) =
= Σ
Σn X
X((ω
ω−−n
nωωs
s)
) w
whhe
erre
e n
n =
= 0
0,, ±
±11,, ±
±22,, .. .. ..
T
Ts n=
=−−∞

s

To reconstruct x(t), you must recover input signal spectrum X(ω) from sampled signal spectrum Y(ω),
which is possible when there is no overlapping between the cycles of Y(ω).

Possibility of sampled frequency spectrum with different conditions is given by the following diagrams:

https://www.tutorialspoint.com/signals_and_systems/signals_sampling_theorem.htm 2/3
1/23/2020 Signals Sampling Theorem - Tutorialspoint

Aliasing Effect

The overlapped region in case of under sampling represents aliasing effect, which can be removed by

considering fs >2fm

By using anti aliasing filters.

https://www.tutorialspoint.com/signals_and_systems/signals_sampling_theorem.htm 3/3

You might also like